ANALISIS AGROINDUSRI DAN STRATEGI PENGEMBANGAN GULA AREN DI DESA RAMBAH TENGAH HULU KECAMATAN RAMBAH KABUPATEN ROKAN HULU PROVINSI RIAU - M.Charizal Purba; Fahrial (DINAMIKA PERTANIAN, 2023)
Palm sugar agro industry can providr an add value to palm sugar producers and overcome labor challenges If the business is managed properly, the purpose of this study is to analysis: the characteristics and profiles of palm sugar producers, palm sugar processing techniques, palm sugar production cost, production, revenue, efficiency, and value added, and make palm sugar marketing strategy. This study used a survey method. The research site was in Rambah Tengah Hulu Village, Rambah District, Rokan Hulu Regency, Riau Province. In this study, 15 producers were selected by snowball sampling. The collected data consisted of primary and secondary data. The method of data analysis used descriptive qualitative analysis and quantitative descriptive. The results showed that the characteristics of palm sugar producers had an average age of 50 years, male gender, 6 years of education level, 10 years of business experience, and the family number of 5 persons. The palm sugar agroindustry was home industry business, private business capital, and labor are come from the family. The process of palm sugar in the research area used simple technology. The cost spent by the producers were Rp. 122,742, revenue Rp. 149,400, profits Rp. 26,658 with an R / C ratio 1.21. The added value obtained from processing palm sugar per process was Rp. 131,400 with a value-added ratio of 87.95%, and a margin value of Rp. 147,400, direct labor income was 0.67%, other input contributions were 10.85%, and profits were 88.46%. Based on the SWOT matrix analysis, it showed that the business was in quadrant I or SO strategy (strengths and opportunities). This strategy shows that the situation is very favorable for entrepreneurs by utilizing their strengths to take advantage of business opportunities.